Assessing the Global Dimension of Sourcing: An Exploratory Study on Italian Companies - Fabrizio Baldassarre; Raffaele Campo (International Journal of Supply Chain Management, 2015)
Companies are paying a growing attention to volatility in the supply chain and many manufacturers are reassessing their global sourcing strategies. Will multinationals retreat to a hemispheric, near-shoring model or opt for a hybrid that maintains an international component? This paper investigates the current challenges for Chief Procurement Officers facing risks and evaluating total costs along the global supply chain. The authors have reviewed both practitioners and academic literature, exploring the main trends in the global approach to supply markets and the trade-offs that could affect strategic sourcing decision in the near future.